Toxicidade e alterações morfofuncionais em Pacu (Piaractus mesopotamicus) exposto ao herbicida Roundup Ready - Shiogiri, Natália Sayuri (2011)
The water body contamination by agrochemical residues is one of the main concerns on the preservation of aquatic biota. The glyphosate is one of the most used herbicides and the Roundup® Ready (RR) formulation has been recently introduced in the market and needs to be evaluated in relation to the possible effects to the aquatic biota. Thus, the aim of this study was to evaluate the toxicity of the herbicide glyphosate in the Roundup® Ready formulation, determining the LC 50;48h and the effects of acute and chronic exposure over the hematologic variables, morphofunctional alterations in gills and liver and responses of the antioxidant defense system in the liver of pacu, Piaractus mesopotamicus. The LC 50;48h of glyphosate in this formulation was estimated in 3,74 mg.L-1, with inferior limit of 3,54 mg.L-1 and superior limit of 3,95 mg.L-1. According to LC 50;48h values, it were defined the quotients stipulating concentrations to be used in the chronic toxicity test. The analyzed alterations in liver of pacus allowed the estimation of the Index of histopathological alterations (IAH), wich ranged between 1,69 to 135,84 in acute test; and between 2,07 to 55,43 in chronic test. In the fishes gills submitted to both tests, acute and chronic, there were no severe alterations. The IAH on gills ranged between 0,29 to 2,07 and no changes were observed in the normal function of the organ. The NKA activity of fishes submitted to both tests presented a medium increase, however it was not significant. Fishes presented a decrease of total number of erythrocytes (RBC) in relation to control, however, hemoglobin concentration, mean cell volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC) increased significantly on fishes submitted to glyphosate exposure in relation to control (p<0,05). The antioxidant enzyme activity of fishes submitted to chronic toxicity test showed a decrease in the specific activity of liver superoxide dismutase and catalase and there was no change in the activity of liver glutathione peroxidase. An increase in the liver lipidic peroxidation was observed after glyphosate exposure. The specific activity of acetylcholinesterase decreased in the brain, but not in the muscle. It was not observed changes in plasma ions concentration. In conclusion, the results of this study shows toxicity of the glyphosate, in the Roundup® Ready formulation, to P. mesopotamicus, which alterations in the animal can compromise the process of detoxification and tissue repair, which may lead the animal to death.